Depressive Symptomatology in Early Retirees Associated With Reason for Retirement—Results From the Population-Based LIFE-Adult-Study - Zuelke, Andrea E.; Roehr, Susanne; Schroeter, Matthias L.; Witte, A. Veronica; Hinz, Andreas; Glaesmer, Heide; Engel, Christoph; Enzenbach, Cornelia; Zachariae, Silke; Zeynalova, Samira; Loeffler, Markus; Villringer, Arno; et al. (Frontiers in Psychiatry, 2020)
Background: Transition from employment to retirement is regarded a crucial event. However, there is mixed evidence on associations between retirement and mental health, especially regarding early retirement. In Germany, cases of early retirement due to ill health – particularly, mental ill health – are increasing. Therefore, we investigated the association between early retirement and depressive symptoms, including information on different types of early retirement. Methods: We analyzed data from 4,808 participants of the population-based LIFE-Adult-Study (age: 40-65 years, 654 retired, 4,154 employed), controlling for sociodemographic information, social network, pre-existing health conditions and duration of retirement. Depressive symptoms were assessed using the Center for Epidemiological Studies Depression Scale. Regression analysis using entropy balancing was applied to achieve covariate balance between retired and employed subjects. Results: We found no overall-differences in depressive symptoms between employed and retired persons (men: b = -.52; p = 0.431; women: b = .05; p = .950). When looking at different types of early retirement, ill-health retirement was linked to increased depressive symptoms in women (b = 4.68, 95% CI = 1.71; 7.65), while voluntary retirement was associated with reduced depressive symptoms in men (b= -1.83, 95% CI = -3.22; -.43) even after controlling for covariates. For women, statutory retirement was linked to lower depressive symptomatology (b = -2.00, 95% CI = -3.99; -.02). Conclusion: Depressive symptomatology among early retirees depends on reason for retirement: For women, ill-health retirement is linked to higher levels of depressive symptoms. Women who retire early due to ill-health constitute a risk group for depressive symptoms that needs specific attention in the health care and social security system.